Update on women in physics in Argentina - Brudny, V. (2013)
Data collected 10 years ago in Argentina concluded that women in physics were underrepresented in many instances and that a «crystal ceiling» was firmly in place. We have collected updated data for several indicators and compared them with those obtained 10 years ago. Although there is not a clear conclusion to be drawn from this comparison, we try to explain the results within the framework of the changes in scientific policies in Argentina.© 2013 American Institute of Physics.